Menapaki Jejak Kebangkitan Pendidikan Islam di Era Pasca Reformasi (1998-2000): Sebuah Kajian Historis - Amy Mustauda; Nafiah Lintang Riyanto; Dody Sugiharto (Tanjak: Sejarah dan Peradaban Islam, 2024)
The history of Islamic education in Indonesia spans from the arrival of Islam and has been influenced by government policies and socio-political dynamics. The Reform era brought significant changes in efforts to renew Islamic education to meet contemporary needs and strengthen Indonesia's national identity. Islamic organizations such as Salafi (Wahhabi), integrated Islamic schools, and the Prosperous Justice Party (PKS) have influenced Islamic educational policies. The research method employed was literature review, a qualitative approach relying on theoretical analysis from scholarly literature. The conclusion highlights that Salafi ideology underpins the establishment of educational institutions and foundations involved in disseminating Wahhabi doctrine through preaching and book publication. This movement has also influenced the formation of Islamic movements in Indonesia. Integrated Islamic schools, pioneered by activists from various campuses, emerged partly due to concerns over children's moral conduct and inadequate parental supervision. Significant changes and reforms include curriculum improvements, enhancement of teacher quality, and educational policies affecting the national education system. The Prosperous Justice Party (PKS), starting from nurturing cadres and campus preaching, has evolved into a influential political force. PKS has laid a strong foundation for Islamic education programs and social initiatives. The influence of PKS is evident in improving the quality of Islamic education at elementary and secondary levels, as well as in shaping a strong Islamic identity among educated middle-class communities.